I colloqui di orientamento per facilitare il successo accademico: una indagine sperimentale - Valeria Biasi; Nazarena Patrizi; Conny De Vincenzo; Mauro Mosca (LED Edizioni Universitarie, 2017)
This article discusses the effectiveness of colloquium for university guidance in facilitating academic success and address the phenomenon of the delay in the studies, which also represents a drop-out risk factor. Before and after the session period of the colloquium for guidance, are administered some questionnaires including the OQ-45 and Lambert Hill (1994; Lo Coco et al., 2008). Participants are divided into an experimental group (80 students completing the guidance session in the first semester), and a control group (52 students placed on the waiting list, who have booked advice for guidance session in the next semester). The characteristics of the participants are described (age, frequented faculty, main areas of discomfort), and data collected show the significant reduction of the symptoms of stress and of the common relational difficulties after the colloquia for university guidance. Data underscore even the efficacy and good stability effects during the follow-up session. Moreover, compared to the control group, students who have done the session path for orientation have showed a significant recovery of the studies. The offer by a university institution of guidance colloquium is one of the many initiatives to facilitate academic success, as well as the setting up of credit recovery courses, the presence of educational support achieved through mentoring and/or online individualized teaching strategies the implementation of paths of re-training orientation.